1980
DOI: 10.1161/01.hyp.2.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Control of arterial pressure and renal function during glucocorticoid excess in dogs.

Abstract: A LTHOUGH adrenal steroids with mineralocorticoid activity are recognized to play an important role in circulatory homeostasis, the importance of the glucocorticoid effects of these steroids in blood pressure regulation, and the mechanisms of glucocorticoid activity on the circulation, are still poorly understood. One observation that suggests glucocorticoids may play a role in blood

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Indeed, in our present study there was a striking loss of salt and water, and a decrease in MAP during cortisol infusion. Accordingly, we have observed in our laboratory 30 (and unpublished data) that chronic infusion of high levels of either cortisol or methylprednisolone (a glucocorticoid with virtually no mineralocorticoid activity) is associated with a decrease in extracellular fluid volume as well as a reduction in arterial pressure. In contrast to cortisol infusion, however, we have observed that chronic ACTH infusion in dogs is associated with an increase in extracellular fluid volume in spite of negative salt and water balance (unpublished data).…”
Section: Discussionmentioning
confidence: 83%
“…Indeed, in our present study there was a striking loss of salt and water, and a decrease in MAP during cortisol infusion. Accordingly, we have observed in our laboratory 30 (and unpublished data) that chronic infusion of high levels of either cortisol or methylprednisolone (a glucocorticoid with virtually no mineralocorticoid activity) is associated with a decrease in extracellular fluid volume as well as a reduction in arterial pressure. In contrast to cortisol infusion, however, we have observed that chronic ACTH infusion in dogs is associated with an increase in extracellular fluid volume in spite of negative salt and water balance (unpublished data).…”
Section: Discussionmentioning
confidence: 83%
“…The increased ^-adrenergic receptor number and response due to glucocorticoid treatment may result in increased potential for vasodilation and, ultimately, lower blood pressure. Indeed, using pure glucocorticoid excess, Hall et al 17 found lower mean arterial pressure in methylprednisolone-treated dogs compared with values in controls.…”
Section: American Heart Associationmentioning
confidence: 98%
“…4 For example, glucocorticoids have been shown either to increase or to decrease blood pressure, 4 -5 to increase renal blood flow, 6 and to reduce vascular smooth muscle contractile responses to prostaglandin (PG) F^ and U46619, a synthetic agonist for the thromboxane A 2 and PG endoperoxide receptor.…”
Section: Onsistent With a Role For Glucocorticoids Inmentioning
confidence: 99%